Riscos nucleares e outros riscos: Avaliação e aceitabilidade - Freire-Maia, Ademar [UNESP] (My University, 1997)
The risks of accidents, illness and early death are part of life on Earth, which touches all living creatures, including Mankind. Because of modern mass communication media, the emotional impact of current risks are greater than in the past. Many unnecessary risks can and should be avoided, and with respect to others, they can be drastically reduced. In addition to this, some risks should be confronted in order to avoid greater ones. In any risk analysis, eventual benefits should be taken into consideration, the risks surrounding other activities, and other factors. Some risks examples and their implications are presented and discussed, in general Nuclear energy is specifically treated, but it also refers and comments that which surrounds other human activities (airplanes, automobiles, smog, gasoline, DDT, and coal energy). As in the history of aviation, nuclear industry has a history of greater successes than failures Nonetheless, in both cases, serious accidents deserve deep thought, including the increment of security norms. The current fear of some people to nuclear energy is compared to the unfounded fear at the advent of gasoline last century Risks, naturally, should not be exagerated, but they cannot be discarded. The main intention of the author is to discuss the complexity of the problem, and to see that risks are evaluated and accepted. In relation to nuclear energy, the author only mentions his point of view, defended in other publications, that it involves very high risks.